Is schizophrenia just a mental illness? - The correlation between schizophrenia and cancer - Wróblewski, Hubert; Chojęta, Dariusz; Zimna, Aleksandra; Zygmunt, Ewelina; Wróblewska, Kinga (Journal of Education, Health and Sport, 2022)
Introduction and purpose of the work:Schizophrenia is a mental illness that affects approximately 24 million people worldwide. It is characterized by hallucinations, most often auditory, delusions, blunted affect, and distortions of thought, such as echoes of thought and perception. There is a predisposition to more frequent diabetes, metabolic syndrome, hormonal disorders, cardiovascular diseases and respiratory diseases, even in patients not treated with antipsychotics. In connection with the above, the question may arise whether schizophrenia also predisposes to developing other diseases, such as cancer. The aim of this article is to present the relationship between the occurrence of schizophrenia and cancer. State of knowledge:There was no correlation between an increased incidence of lung cancer and schizophrenia, however, the analyzed studies were not homogeneous. In the case of breast cancer, data suggest a higher incidence of breast cancer among people with psychiatric disorders. In prostate cancer, a lower risk of developing the disease has been reported in patients with schizophrenia. It should be noted that despite the predisposition of people with schizophrenia to addiction to stimulants, low physical activity, the increase in the risk of cancer in some studies was not very high. Summary: It can be noticed that there is a correlation between the occurrence of schizophrenia and the predisposition to developing malignant neoplasms. Currently, hope is placed on their use in anti-cancer therapy.